An analysis of the impact of the economic crisis on child refugee protection in Zimbabwe from 2000 – 2017. - Mavura, Tanyaradzwa Lloyd (Midlands State University, 2020)
There has been a lot of bickering on the economic situation in Zimbabwe, the precipitous slide of the economy have had far reaching effects on the political, economic and social life of the people residing in Zimbabwe. This study explores the impact of the economic crisis on child refugees from a broader economic, political and social perspective. A case study of Zimbabwe and in particular Tongogara refugee camp was used for purposes of this study. Through literature review, a lot of writings showed that the economic crisis have affected Zimbabwe’s compliance to its international obligations in setting up child refugee initiatives. A case study research design approach which triangulates both qualitative and quantitative research methodologies into mixed methods was utilized in order to present both statistical, content and thematic analysis of the findings to legitimize and clarify key issues concerning the nexus between the economic crisis and child refugee suffering in Zimbabwe. The research findings reviewed that, the economic crisis was largely of our own making since independence as poor policing strategies and weak policy implementation affected the economy of Zimbabwe. However a large sample of the respondents that where surveyed and interviewed, expressed that the economic crisis have had negative effects on child refugee protection programmes and policies which resulted in the suffering and abuse of refugee minors. Through results acquired from experts and refugee communities, the research reviewed that there is need for the government and its relative partners to strengthen it legislative frameworks and repeal its policies to ensure that the economy is on the right track and enable it to sustain the needs of refugee minors, and hence the need to undergo further research to initiate a separate budget reserved for refugee children. The research discoveries led to a conclusion that the economic crisis have been, and will always be of negative influence to child refugee protection if proper considerations, strategies and policies are not put in place as the country will continue to face financial challenges in the long run.